A Practical Approach to the "Leaning" Column - Geschwindner, Louis F. (Engineering Journal, 1995)
The "leaning" column has existed as an element in steel structures from the time steel frames were first constructed. Although they provide the title for this paper, they themselves are not the problem which needs to be addressed. It is their impact on the other parts of the structure which must be a consideration in any design. A "leaning" column is a pin ended column which has no lateral stability of its own; thus, it must rely on other parts of the structure to provide for its lateral stability and the lateral resistance for the entire frame. This paper will discuss the situations in which "leaning" columns will occur and look at practical ways to account for them in both LRFD and ASD design.